Venous thromboembolism syndrome in gynecological cancer. (1st January 2006) - Wang, X.; Fu, S.; Freedman, R. S.; Kavanagh, J. J.
Abstract : Venous thromboembolism (VTE) could be presented as an initial clinical feature in some cancer patients or a complication followed by various cancer treatments, which all indicates a poor outcome. This review focuses on elucidating the relationship of VTE and the main gynecological cancers including ovarian, endometrial, and cervical cancers. First, the general VTE information about gynecological cancer are introduced; second, the risk factors of VTE developing in gynecological cancer were discussed; third, we do a retrospective analysis on a novel treatment targeting coagulation cascade; and last, we analyze VTE as a remarkable complication followed by recombinant human erythropoietin and anti–vascular endothelial growth factor treatment in gynecological cancer patients. In summary, the interaction between the coagulation system and cancer progression is a novel promising area to be explored in the study of VTE in patients with gynecological cancer.